Why Do Doctoral Students Struggle to Finish? A Phenomenological Exploration of PhD Completion Dynamics - Erasto Kano (Managere: Indonesian Journal of Educational Management, 2026)
Doctoral completion remains a persistent challenge in many higher education systems, particularly within developing contexts where adequate academic support structures have not always accompanied institutional expansion. This study explores the dynamics shaping PhD completion at the University of Dodoma, Tanzania, using a qualitative phenomenological approach that centres doctoral students’ lived experiences. The research aims to understand how institutional, personal, supervisory, and systemic factors interact to influence doctoral progression and completion outcomes. Data were collected through semi-structuredsemi-structured interviews with 35 PhD candidates from diverse academic disciplines and analysed using inductive thematic analysis. The findings reveal that doctoral completion is not a linear process determined solely by individual effort but is shaped by interconnected pressures operating across multiple levels. Institutional barriers such as bureaucratic procedures, limited research facilities, and rigid programme structures were found to slow academic progress. Personal challenges, including financial constraints, competing professional responsibilities, and psychological pressures, emerged as the most frequently experienced obstacles. Supervisory dynamics, particularly delayed feedback and heavy supervisory workloads, significantly influenced motivation and research continuity, while systemic publication requirements intensified pressure during advanced stages of candidature. The study highlights that doctoral completion should be understood as an ecological process requiring coordinated institutional and policy responses rather than student-focused interventions alone. These findings provide practical insights for higher education management and policymakers seeking to improve doctoral completion rates through supportive academic environments and integrated supervision practices.